1995
DOI: 10.1002/ijch.199500035
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Activated Rhodopsin

Abstract: Abstract. After cis/trans isomerization of retinal and early photoproducts, activated rhodopsin (R*) develops signaling states for different proteins in a time-ordered sequence. Rhodopsin kinase binds all Meta forms, including the early Meta I, while interaction with transducin (G,) or arrestin requires the deprotonated Schiff base form, Meta II (MIl). G, recognizes a specific conformation, termed MIl b , which arises from an additional, spectrally silent conversion, linked to proton uptake. Collisional coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 192 publications
1
49
0
Order By: Relevance
“…MII is the catalytically active intermediate of photoexcited rhodopsin (R*) (1,5,6). We went on to examine whether binding to MII by the two peptides would inhibit Gt activation as expected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MII is the catalytically active intermediate of photoexcited rhodopsin (R*) (1,5,6). We went on to examine whether binding to MII by the two peptides would inhibit Gt activation as expected.…”
Section: Resultsmentioning
confidence: 99%
“…We can now propose that the increasing rate of Gt activation with increasing pH in the acidic branch of the profile reflects the pH dependency of microscopic recognition of domains, which occurs independently of the specific geometry in which they are arranged in conformations MIIa and MIIb, respectively. The decreasing rate at high pH can consistently be attributed (4) to the pH-dependent formation (6,21) of the receptor conformation termed MIIb, which satisfies the grossstructural constraints of catalytic receptor͞G-protein interaction. Although we believe that MIIa is a necessary step in reaching rhodopsin's active conformation (39), its role in nucleotide exchange catalysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found that this structural evolution includes a retinal counterion switch from Glu113 in the dark state to Glu181 in the metarhodopsin I (Meta I) state (19). The Schiff base is then deprotonated upon Meta II formation, and Meta II couples with transducin to trigger the visual signal cascade (20,21).…”
mentioning
confidence: 99%
“…Absorption of light transforms rhodopsin (rho) into an activated state, which interacts with a heterotrimeric G protein to initiate an enzyme cascade leading to visual transduction. To reach this active state, called metarhodopsin (meta) II (1,2), rho passes through a number of intermediates that have been characterized by UV-visible, Fourier-transform infrared (FTIR), Raman, and NMR spectroscopies, in addition to spin-labeling and biochemical studies (3)(4)(5)(6)(7)(8)(9)(10). One way to characterize the intermediates is to trap them at low temperatures.…”
mentioning
confidence: 99%